Herbal medicine uses to treat people with epilepsy: A survey in rural communities of northern Peru. (6th April 2018) - Auditeau, Emilie; Moyano, Luz Maria; Bourdy, Geneviève; Nizard, Mandy; Jost, Jérémy; Ratsimbazafy, Voa; Preux, Pierre-Marie; Boumediene, Farid
Abstract: Ethnopharmacological relevance: Epilepsy affects 150, 000 people in Peru, with a prevalence of 16.6/1000 and a treatment gap of 75%. Herbal medicine (HM) is widely used in this country. Aim of the study: We aimed to assess the use of plants in a rural community in northern Peru as part of therapeutic strategies for people with epilepsy (PWE). Materials and methods: The study was a cross-sectional observational and descriptive study. The inclusion criteria for people with epilepsy were 2 years of age and over, having lived in the study area for at least 3 months and a confirmed diagnosis of epilepsy by a neurologist. The information was gathered through structured interviews using a survey questionnaire. Botanical species used by people with epilepsy or traditional healers were collected and identified. Results: Out of the 228 people with epilepsy included, 60.0% had used herbal remedies and 54.8% both herbal medicine and anti-epileptic drugs. The traditional healer was the first practitioner consulted by 45.2% of people with epilepsy. Sixty-six species have been mentioned by the people with epilepsy and traditional healers on the treatment of epilepsy. Carbamazepine was the most prescribed anti-epileptic drug with 33.2% of prescriptions. Conclusions: This study was the first to measure a percentage of use of herbal medicine for epilepsy in Peru. It would be interesting to conduct a pharmacological evaluation of the most commonly used species on epileptic models to validate and secure their use. Graphical abstract: fx1